Characterisation of human diaphragm at high strain rate loading. (July 2016) - Gaur, Piyush; Chawla, Anoop; Verma, Khyati; Mukherjee, Sudipto; Lalvani, Sanjeev; Malhotra, Rajesh; Mayer, Christian
Abstract: Motor vehicle crashes (MVC׳s) commonly results in life threating thoracic and abdominal injuries. Finite element models are becoming an important tool in analyzing automotive related injuries to soft tissues. Establishment of accurate material models including tissue tolerance limits is critical for accurate injury evaluation. The diaphragm is the most important skeletal muscle for respiration having a bi-domed structure, separating the thoracic cavity from abdominal cavity. Traumatic rupture of the diaphragm is a potentially serious injury which presents in different forms depending upon the mechanisms of the causative trauma. A major step to gain insight into the mechanism of traumatic rupture of diaphragm is to understand the high rate failure properties of diaphragm tissue. Thus, the main objective of this study was to estimate the mechanical and failure properties of human diaphragm at strain rates associated with blunt thoracic and abdominal trauma. A total of 23 uniaxial tensile tests were performed at various strain rates ranging from 0.001–200 s −1 in order to characterize the mechanical and failure properties on human diaphragm tissue. Each specimen was tested to failure at one of the four strain rates (0.001 s −1, 65 s −1, and 130 s −1, 190 s −1 ) to investigate the effects of strain rate dependency. High speed video and markers placed on the grippers were used to measure the gripper to gripper displacement. Engineering stresses reported in the study is calculated from the ratio of force measured and initial cross sectional area whereas engineering strain is calculated from the ratio of the elongation to the undeformed length (gauge length) of the specimen.The results of this study showed that the diaphragm tissues is rate dependent with higher strain rate tests giving higher failure stress and higher failure strains. The failure stress for all tests ranged from 1.17 MPa to 4.1 MPa and failure strain ranged from 12.15% to 24.62%. Graphical abstract: Highlights: No uniaxial or biaxial tensile test data is available for human diaphragm in literature. New strain rate dependent mechanical properties of human diaphragm are presented. Mechanical behaviour of diaphragm has been studied and examined under varying strain rates. Diaphragm properties obtained are of value for use in Finite Element models.